Upaya SDN Pangeran 3 Banjarmasin dalam Mengadaptasi Kurikulum Merdeka di Tengah Tantangan Internal dan Eksternal - Siregar, Rima Nur Azizah; Firlana, Hanif; Hafizah, Rini; Noorkhalisah, Noorkhalisah; Pratiwi, Diani Ayu (ARZUSIN, 2025)
The implementation of the Merdeka Curriculum at the primary education level is a strategic step in addressing the challenges of 21st-century education, which demands flexibility, creativity, and contextual learning. This study aims to examine the adaptation process of the Merdeka Curriculum at SDN Pangeran 3 Banjarmasin, a school with limited resources but showing strong initiative in its implementation. Using a qualitative approach with a case study method, data were obtained through in-depth interviews, direct observations, and documentation. The results indicate that although the teachers at this school face challenges such as limited access to training, inadequate facilities, and restricted financial support, they are able to creatively and contextually implement the Merdeka Curriculum. Strategies such as project-based learning (P5), utilizing local learning resources, and informal collaboration among teachers have been key to success. Supportive leadership from the principal and a culture of gotong royong (collective work practice) in the school environment also contribute to the sustainability of this curriculum adaptation. These findings emphasize that the success of the Merdeka Curriculum implementation relies not only on the availability of infrastructure but also on the resilience, creativity, and collaboration of educators. This study recommends strengthening flexible and equitable teacher training, as well as affirmative policies for small schools, so that curriculum implementation can proceed in a more inclusive and sustainable manner.